Clinical indications for image-guided interventional procedures in the musculoskeletal system: a Delphi-based consensus paper from the European Society of Musculoskeletal Radiology (ESSR)-part IV, hip - Sconfienza, Luca Maria; Adriaensen, Miraude; Alcala-Galiano, Andrea; Allen, Georgina; Aparisi Gómez, Maria Pilar; Aringhieri, Giacomo; Bazzocchi, Alberto; Beggs, Ian; Chianca, Vito; Corazza, Angelo; Dalili, Danoob; De Dea, Miriam; et al. (Springer Science and Business Media LLC, 2022)
Image-guided musculoskeletal interventional procedures around the hip are widely used in daily clinical practice. The need for clarity concerning the actual added value of imaging guidance and types of medications to be offered led the Ultrasound and the Interventional Subcommittees of the European Society of Musculoskeletal Radiology (ESSR) to promote, with the support of its Research Committee, a collaborative project to review the published literature on image-guided musculoskeletal interventional procedures in the lower limb in order to derive a list of clinical indications.
Keywords: Interventional radiology; Hip; Ultrasonography; Injections; Platelet-rich plasma